Implementation of the PIECES Framework as an Evaluation of Student Satisfaction Levels with the Use of STARS UKSW - Muflihanto, Ezar Juan; Hartomo, Kristoko Dwi (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
This research aims to evaluate the level of student satisfaction with the use of the Academic Information System (STARS) at Satya Wacana Christian University (UKSW) using the PIECES (Performance, Information, Economy, Control, Efficiency, and Service) framework. The research method used was a survey with a structured questionnaire distributed to a sample of students from various study programs at UKSW. The collected data was analyzed using descriptive statistical techniques and the PIECES Framework to measure STARS performance from the user's perspective. The research results show that although STARS has provided good performance in several aspects, there are areas that require improvement to increase user satisfaction. The implication of this research is the importance of using a framework such as PIECES in evaluating information systems to thoroughly understand user needs and perceptions, as well as providing a strong basis for improvement and development of better systems in the future.